Long-Term Mechanical Ventilation in Neonates: A 10-Year Overview and Predictive Model - Sauthier, Michaël; Sauthier, Nicolas; Bergeron Gallant, Krystale; Lodygensky, Gregory A.; Kawaguchi, Atsushi; Emeriaud, Guillaume; Jouvet, Philippe (Frontiers in Pediatrics, 2021)
Objectives: Significant resources are devoted to neonatal prolonged mechanical ventilation (NPMV), but little is known about the outcomes of those children. Our primary objective was to describe NPMV respiratory, digestive and neurological outcomes at 18-month corrected age. Our second objective was to early identify among the NPMV cohort, which patients will need to be ventilated ≥125 days, which corresponded to the 75th percentile in preliminary data and describe that subgroup. Methods: In this retrospective cohort study, we included all children born between 2004 and 2013 who had a NPMV (≥21 days of invasive or noninvasive respiratory support reached between 40 and 44 weeks of postconceptional age). We used random forests, logistic regression with penalization, naive Bayes and XGBoost to predict which patients will need ≥125 days of ventilation. We used a Monte Carlo cross validation. Results: We included 164 patients with 40% (n=66) female, median gestational age was 29 weeks (interquartile range [IQR] 26-36 weeks) with a bimodal distribution. Median ventilation days were 104 (IQR 66-139 days). Most frequent associated diagnoses were pulmonary hypertension (43%), early pulmonary dysplasia (41%) and lobar emphysema (37%). At 18 months corrected age, 29% (n=47) had died, 59% (n=97) were free of any respiratory support and 45% (n=74) were exclusively orally fed. A moderate area under the ROC curve of 0.65 (95% CI: 0.54-0.72) for identifying patients ≥125 days of ventilation at inclusion was achieved by random forests classifiers. Among the 26 measured at inclusion, the most contributive ones were PCO2, inspired O2 concentration and gestational age. At 18 months corrected age, patients ventilated ≥125 days had a lower respiratory weaning success (76% vs. 87%, P=0.05), lower exclusive oral feeding proportion (51% vs. 84%, P<0.001) and a higher neurological impairment (median Pediatric Cerebral Performance Category score 3 vs. 2, P=0.008) than patients ventilated <125 days. Conclusion: NPMV is a severe condition with a high risk of mortality, neurological impairment and oral feed delay at 18 months. Most survivors were weaned of any respiratory support. We identified risk factors that allow early identify the most at-risk children of long-term ventilation with a moderate discrimination.